Climate variability drives recent tree mortality in Europe. (12th June 2017) - Neumann, Mathias; Mues, Volker; Moreno, Adam; Hasenauer, Hubert; Seidl, Rupert
Abstract: Tree mortality is an important process in forest ecosystems, frequently hypothesized to be highly climate sensitive. Yet, tree death remains one of the least understood processes of forest dynamics. Recently, changes in tree mortality have been observed in forests around the globe, which could profoundly affect ecosystem functioning and services provisioning to society. We describe continental‐scale patterns of recent tree mortality from the only consistent pan‐European forest monitoring network, identifying recent mortality hotspots in southern and northern Europe. Analyzing 925, 462 annual observations of 235, 895 trees between 2000 and 2012, we determine the influence of climate variability and tree age on interannual variation in tree mortality using Cox proportional hazard models. Warm summers as well as high seasonal variability in precipitation increased the likelihood of tree death. However, our data also suggest that reduced cold‐induced mortality could compensate increased mortality related to peak temperatures in a warming climate. Besides climate variability, age was an important driver of tree mortality, with individual mortality probability decreasing with age over the first century of a trees life. A considerable portion of the observed variation in tree mortality could be explained by satellite‐derived net primary productivity, suggesting that widely available remote sensing products can be used as an early warning indicator of widespread tree mortality. Our findings advance the understanding of patterns of large‐scale tree mortality by demonstrating the influence of seasonal and diurnal climate variation, and highlight the potential of state‐of‐the‐art remote sensing to anticipate an increased likelihood of tree mortality in space and time. Abstract : We identified recent tree mortality hotspots using more than 200.000 forest monitoring observations from across Europe. Seasonal variability in summer and winter temperatures as well as shifts of precipitation between seasons enhance the mortality risk, while increasing tree age reduces the likelihood for tree death. In a warming climate elevated mortality due to high peak temperatures could be offset by reduced cold‐induced mortality. Remotely sensed productivity can be used to foresee future mortality events.